I2O5 promoted iodosulfenylation of indoles under metal-free conditions. Issue 29 (18th July 2019) - Wang, Wangyang; Zhu, Fuyuan; Yan, Zhaohua; He, Mingchuang; Lin, Sen
Graphical abstract: Highlights: One-step synthesis of difunctionalization product 3-arylthio-2-iodoindoles. I2 O5 promoted iodosulfenylation of indoles. Iodosulfenylation of indoles was reported for the first time. Metal-free and non-peroxide conditions were used. Abstract: A mild, efficient, and metal-free strategy to construct 2-iodo-3-arylthioindoles was developed via I2 O5 -promoted iodosulfenylation of indoles utilizing simple, cheap and easily available thiophenols as sulfur sources. It is the first time that the iodothiolation difunctionalization of indoles at C-2 and C-3 positions was accomplished with the formation of 2-iodo-3-arylthioindoles in moderate to good yields.